SOSIALISASI DAN EDUKASI DAGUSIBU PADA KELOMPOK IBU RUMAH TANGGA DI KECAMATAN DAU - Novia Maulina; Abdul Hakim; Fitriyani Fitriyani; Burhan Ma'arif (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Health promotion is the process by which a community makes efforts to improve its ability to optimize the factors that affect health. In addition to positive impacts, advances in science and technology in the pharmaceutical industry also have negative impacts, one of which is obtaining, using, storing, and disposing of drugs in the wrong way. “Dapatkan, Gunakan, Simpan, Buang” (DAGUSIBU) is a Drug Awareness Family Movement initiated by the Indonesian Pharmacists Association (IAI) in an effort to provide public understanding and awareness of the correct use of drugs. This community service was carried out with the aim of socializing and educating the housewives' community group in Dau sub-district, Malang Regency, about DAGUSIBU. The method used is quantitative with a quasi-experimental design with a one-group pretest and posttest with active and participatory learning methods through door-to-door socialization activities with media leaflets. The results show that most respondents are aged 31–35 years (23.8%), and the distribution of DAGUSIBU drug knowledge among respondents has increased by 66.6% after socialization and education activities.